(untitled) (Tempo e Argumento, 2010)
The penitentiary world has been the object of a variety of studies in the most diverse areas of knowledge and still maintains itself poorly understood. This is due particularly to the barriers that are imposed to the researchers in the gaining of direct contact with prisoners and primary data sources. In this sense this work, developed during the Master dissertation studies in Environment Sciences in the Federal University of Tocantins (UFT), presents a plus in the analysis by including 960 notes written by men held in prison, in the provisory detain house of Palmas. The purpose of this article is to present an interpretation of the quotidian life in prison by means of interpretation of note readings written by the inmates. In a unique manner, we tried to understand the mechanisms used by these men to maintain a link between life in prison and the one external to it. Seen in a self perspective of writing (GOMES, 2004), the notes reveal much of the quotidian of prisoners in the house of prison: their problems, conduct, privations and anguishes.